An integrated approach to solving the problems of establishing the prescription of the application of handwritten and printed requisites of documents - Shesteperova, Elena Lukinichna; Orlovskaya, Rita Konstantinovna (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The purpose of this study is to reveal the advantages of the integrated approach to the fulfillment of expertise in the framework of technical examination of documents requisites and materials. The authors, using the main research methods measuring, microscopic, photographic, chromatographic, spectrophotometric, X-ray microanalysis, describe their work experience supporting conclusions with photographs from practical material of the forensic technical examination of documents.
Keywords: questioned document examination; an integrated document study; relative age of execution of the document; microscopic examination; aggressive impact on the requisites of the document